IbM HARMONI KECERDASAN UNTUK JANIN MELALUI IBU HAMIL - Risqi Dewi Aisyah; Fitriyani Fitriyani; Suparni Suparni (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Intelligence with a range of definitions related to the brain at the last findings stated that the stimulation will increase the potential of intelligence when performed while pregnant and early life.  Lack of brain stimulation at the time of pregnancy can cause the inability of children to learn and adapt to the demands of society. In pregnancy the mother can  do a Fetal stimulation through classical voices that will form the regular vibration stimulation that can provide sensing, organs and emotions. The purpose of this IbM is an increase in knowledge and practice of stimulation on the fetus in an effort to improve the quality of the brain on the fetus allowing the increased potential of intelligence in children.  IBM was conducted in three villages with a population of participants 44 pregnant women.  The result of that the IbM education conducted this IbM increasing knowledge of pregnant women with a Ttest p value obtained = 0.026. There is a difference of knowledge before and after done IbM. Advice formidwives, to provide education on pregnant omen how member stimulation in infants to increase intelligence in accordance with program guide Brain Booster.Keyword : Pregnant Women, Fetal Intelligence